Effectiveness of High Fidelity Video-Assisted Real-Time Simulation: A Comparison of Three Training Methods for Acute Pediatric Emergencies - Ester H. A. J. Coolen; Jos M. T. Draaisma; Marije Hogeveen; Tim A. J. Antonius; Charlotte M. L. Lommen; Jan L. Loeffen (International Journal of Pediatrics, 2012)
Background. Video-assisted real-time simulation (VARS) offers the possibility of developing competence in acute medicine in a realistic and safe environment. We investigated the effectiveness of the VARS model and compared it with educational methods like Problem-Based Learning (PBL) and Pediatric Advanced Life Support (PALS). Methods. 45 fourth-year medical students were randomized for three educational methods. Level of knowledge and self-efficacy were measured before and after intervention. Clinical performance was measured by a blinded observer using a video checklist of prescripted scenarios on a high-fidelity simulator. Results. Knowledge test and self-efficacy scores improved significantly (𝑃<0.001) without differences between educational groups. The VARS group showed significantly (𝑃<0.05) higher scores on both postintervention scenarios concerning structure and time. Conclusion. VARS training is an effective educational method teaching pediatric acute care skills in the undergraduate curriculum. When compared to PBL and PALS training, VARS training appears to be superior in enhancing short-term clinical performance.